Analysis of factors associated with abnormal thyroid function among medical staff in radiotherapy departments - Ren, Ziwei; Ren, Yanwei; Bai, Xinghua; Shang, Puyu; Li, Guang (Frontiers in Public Health, 2023)
Objective To understand the abnormal thyroid function and its associated factors among medical staff in radiotherapy departments. Methods Data related to medical staff in radiotherapy departments who met the inclusion and exclusion criteria were analyzed from September to December 2022 in Shenyang, Liaoning Province, including basic personal and lifestyle habits, work information, and scores on the Depression Self-Assessment Scale, Perception Stress Scale and the Generalized Anxiety Scale. Data analysis was performed using  2 test and binary logistic regression. Results Among 484 medical staff in the radiotherapy department, 147 (30.4%) had abnormal thyroid function. Binary logistic regression analysis showed that age, years of work, smoking, occupational exposure, smoking, late-night snacking habits, depression, and stress perception were associated factors for abnormal thyroid function among medical staff in radiotherapy departments, and physical exercise was a protective factor for abnormal thyroid function among medical staff in radiotherapy departments. Conclusion The positive rate of thyroid dysfunction among medical personnel in the radiology department is relatively high. It is necessary to strengthen health education and publicity for relevant practitioners, and improve the coverage of occupational disease prevention and control education.